NEW RELIGIOUS CURRENTS AND THEIR INFLUENCE: https://doi.org/10.5281/zenodo.15316135 - Kuramatov , Murod (Journal of International science networks, 2025)
New religious currents, often referred to as New Religious Movements (NRMs), represent a diverse array of spiritual expressions that have emerged in response to significant societal changes and evolving spiritual needs. These movements are characterized by their eclectic and syncretic nature, drawing upon various religious traditions and cultural influences to form unique belief systems that resonate with contemporary seekers.